Hypoxia potentiates monocyte-derived dendritic cells for release of tumor necrosis factor α via MAP3K8. Issue 6 (14th December 2018) - Paardekooper, Laurent M.; Bendix, Maura B.; Ottria, Andrea; de Haer, Lieke W.; ter Beest, Martin; Radstake, Timothy R.D.J.; Marut, Wioleta; van den Bogaart, Geert
Abstract : Dendritic cells (DCs) constantly sample peripheral tissues for antigens, which are subsequently ingested to derive peptides for presentation to T cells in lymph nodes. To do so, DCs have to traverse many different tissues with varying oxygen tensions. Additionally, DCs are often exposed to low oxygen tensions in tumors, where vascularization is lacking, as well as in inflammatory foci, where oxygen is rapidly consumed by inflammatory cells during the respiratory burst. DCs respond to oxygen levels to tailor immune responses to such low-oxygen environments. In the present study, we identified a mechanism of hypoxia-mediated potentiation of release of tumor necrosis factor α (TNF-α), a pro-inflammatory cytokine with important roles in both anti-cancer immunity and autoimmune disease. We show in human monocyte-derived DCs (moDCs) that this potentiation is controlled exclusively via the p38/mitogen-activated protein kinase (MAPK) pathway. We identified MAPK kinase kinase 8 (MAP3K8) as a target gene of hypoxia-induced factor (HIF), a transcription factor controlled by oxygen tension, upstream of the p38/MAPK pathway. Hypoxia increased expression of MAP3K8 concomitant with the potentiation of TNF-α secretion. This potentiation was no longer observed upon siRNA silencing of MAP3K8 or with a small molecule inhibitor of this kinase, and this also decreased p38/MAPK phosphorylation. However, expression of DC maturation markers CD83, CD86, and HLA-DR were not changed by hypoxia. Since DCs play an important role in controlling T-cell activation and differentiation, our results provide novel insight in understanding T-cell responses in inflammation, cancer, autoimmune disease and other diseases where hypoxia is involved.